THE MODIFICATION OF THE RRT ALGORITHM FOR THE OPTIMAL TRAJECTORY DETERMINING OF THE MOTION VEHICLE WITH THE OBSTACLES AVOIDANCE - I. Z. Akhmetzyanov; M. A. Ionov; V. S. Karabcev (Вестник СибАДИ, 2018)
The problem of planning the motion path of an unmanned vehicle is presented in the article. The results of development and the software  implementation, and the research of the algorithm for constructing quasi- optimal trajectory of an unmanned vehicle in a known environment are  shown. The RRT standard algorithm as the basis for the path construction  between two points is used in the article. To improve the efficiency, the basic  algorithm of the following modifications such as the orientation to the finish  point, the removal of intermediate vertices are introduced. The orientation to the finish point allows to check the possibility of the direct connection to the last point which could be found by the RRT algorithm. The orientation also  reduces the trajectory searching, because the basic RRT algorithm searches  the point until a randomly generated point appears in the vicinity of the  finish line. The deleting process of the intermediate vertices is carried out for such route sections where the trajectory could be straighten by the  intermediate vertices’ removing without crossing the obstacles. The  consideration of the kinematic constraints on the minimum turning radius of  the vehicle, which is based on the Dubins curves is implemented in the  article. As a result of all these algorithm modifications, its performance has  been increased about 30% according to the computer simulation results.